2021
DOI: 10.3390/cells10020302
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone: A Tie-Breaker in SARS-CoV2-Infected Cancer Patients?

Abstract: Since the beginning of the SARS-CoV-2(severe acute respiratory syndrome-coronavirus-2) pandemic, arace to develop a vaccine has been initiated, considering the massive and rather significant economic and healthcare hits that this virus has caused. The pathophysiology occurring following COVID-19(coronavirus disease-2019) infection has givenhints regarding the supportive and symptomatic treatments to establish for patients, as no specific anti-SARS-CoV-2 is available yet. Patient symptoms vary greatly and range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 295 publications
(392 reference statements)
0
11
0
3
Order By: Relevance
“…Genes demonstrating in pathways of cancer and in viral life cycle indicate that TQ has roles for both anti-cancers and anti-viruses. Interestingly, recent studies found that TQ might have inhibitory potential against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) protease ( 29 ), particularly for cancer patients ( 30 ). As we know, novel virus SARS-CoV-2 causes coronavirus disease 2019 (COVID-19), and the World Health Organization (WHO) declared COVID-19 as a global pandemic as earlier of March 11, 2020 ( 31 – 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Genes demonstrating in pathways of cancer and in viral life cycle indicate that TQ has roles for both anti-cancers and anti-viruses. Interestingly, recent studies found that TQ might have inhibitory potential against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) protease ( 29 ), particularly for cancer patients ( 30 ). As we know, novel virus SARS-CoV-2 causes coronavirus disease 2019 (COVID-19), and the World Health Organization (WHO) declared COVID-19 as a global pandemic as earlier of March 11, 2020 ( 31 – 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thymoquinone also decreases the expression of GRP78 and the ACE2 receptor, thereby reducing viral entry. This shows that thymoquinone has the potential to reduce SARS-CoV-2 infection [ 169 ].…”
Section: Natural Antioxidant Therapies For Activating Nrf2mentioning
confidence: 99%
“…6 IC 50 AE SD (mM, n ¼ vivo rat model. 42 Moreover, Hettiarachchi et al revealed the very toxicity of CB [5] and CB [7] and high cell tolerance at concentrations of up to 1 mM when tested against normal human cell lines originated from kidney, liver, and blood tissues. 43…”
Section: Cytotoxicitymentioning
confidence: 99%
“…2 Recently, TQ showed a potential inhibition activity against coronavirus infections. 4,5 Despite the promising therapeutic efficiency of TQ, the lack of bioavailability, pharmacokinetic parameters, and formulation problems deferred the usage of TQ in the clinical development. 3 The bioavailability problem (for example, poor solubility in water) is mainly related to the fact that TQ is a hydrophobic molecule.…”
Section: Introductionmentioning
confidence: 99%